2021
DOI: 10.3390/jmse9070705
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Correlation between Soil Consolidation and Pile Set-Up Considering Pile Installation Effect

Abstract: In saturated fine-grained soil, the development and dissipation of excess pore water pressure (EPWP) during and after pile jacking change the effective stress of the surrounding soil, and thereby affect the pile set-up. In this paper, the entire process of steel-pipe pile jacking (the installation process and the subsequent consolidation phase) is simulated with three-dimensional (3D) finite element models, considering the pore water effect. After the model verification, a comprehensive numerical analysis was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Nine (9) papers are included in this Special Issue: one review article [1] and eight research articles covering two main themes-(1) the mechanisms of marine sediments in the Yellow River Delta [2] and a field study [3] and (2) structure-seabed interactions in the vicinity of tunnels [4,5], spudcans [6], pile foundations [7], breakwaters [8], and pipelines [9]. More details on each contribution are summarized here.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nine (9) papers are included in this Special Issue: one review article [1] and eight research articles covering two main themes-(1) the mechanisms of marine sediments in the Yellow River Delta [2] and a field study [3] and (2) structure-seabed interactions in the vicinity of tunnels [4,5], spudcans [6], pile foundations [7], breakwaters [8], and pipelines [9]. More details on each contribution are summarized here.…”
mentioning
confidence: 99%
“…Pile-type foundations have been used to support various offshore infrastructures, such as platforms, cross-sea bridges, etc. In this paper, Dou et al [7] attempts to simulate the entire process of steel-pipe pile jacking in saturated fine-grained soil. Based on numerical simulation, it was concluded that during pile installation, the negative excess pore-water pressure near the ground surface around the pile and at a certain depth below the pile tip would increase the effective stress and hence the penetration resistance.…”
mentioning
confidence: 99%
“…However, the soil's mechanical properties and the distribution of soil layers also have an impact on changes in pore water pressure [16,18], but similar boundary-scale responses have been observed when piles are driven in non-typical soils, like diatomaceous earth, which has a high intra-particle porosity, complex particle shapes, and uniform mineralogy [19]. During pile driving, negative surplus pore pressure around the pile close to the ground surface and below a certain depth beneath the pile tip will increase effective stress, hence increasing penetration resistance [20].…”
Section: Introductionmentioning
confidence: 77%
“…Numerous studies have tried to model the pore water response to pile installation or even other construction vibrations in the near-field analytically [5,30,31]. The initial stresses in the sandy soil before the pile is driven are the horizontal effective stress (𝜎 3 ), the vertical effective stress (𝜎 1 ), and the pore pressure (𝑈).…”
Section: Effect On Pore Water Pressurementioning
confidence: 99%